Spatial Pattern, Transportation and Air Quality Nexus: The Case of Iskandar Malaysia (International Journal of Built Environment and Sustainability, 2016)
Spatial pattern, transportation, and air quality are three development entities which significantly affecting one another. This nexus exhibits the urbanization imprint accouter transportation generating air pollution as a reflection of spatial distribution. The integration among them is a vital part of development as it affects the societal living environment. It provides unfavorable air quality and directly cause health problems. The developing region of Iskandar Malaysia exhibits huge spatial distribution transformation accompanied by large percentage of urbanization rate, but seems less integration of land use and transportation planning which causes the exaggeration of air pollution. We carry out the research on the nexus of spatial distribution, transportation and air quality in Iskandar Malaysia by analyzing and evaluating the interconnectivity of these three entities. The spatial analysis and evaluation on the land use development pattern and spatial policy shows that the Iskandar development region are growing in the polycentric manners, where the spatial development policy drives the distributional growth of new sub-centers. We undertook a household-based travel survey that reveals the poly-centricity reflected by the de-concentration of workplaces which shifted from the single point towards multiple centers. On the other hand, this phenomenon has created a distributional traffic pattern amid the high dependency on the private vehicles of the citizens in Iskandar Malaysia. With a predominantly fossil fuel consuming vehicles, this has generated air pollution. Based on the traffic survey and the dependency of the citizens on private cars for their daily mobility, the concentration of air pollution is seemingly at risk. This research reflects that Iskandar Malaysia development region currently undergoes towards polycentric development with some new urban centers. We found that land use and transportation planning policies require serious attention as the current trend of spatial pattern development tends to reinforce high dependency on the motorized travel.